1995
DOI: 10.1007/bf01690995
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to diphtheria in Northern Norway and Northwestern Russia

Abstract: A case of diphtheria, which has not been seen in Norway for 30 years, was reported in 1992 in the northern part of the country bordering Russia. An increasing number of cases of diphtheria has been reported in the former USSR, including the northwestern part of Russia. In order to elucidate the potential of an epidemic spread across the Norwegian-Russian border, a seroepidemiological study was performed. A total of 470 sera, 243 from Finnmark, Norway, and 227 from Arkhangelsk, Russia, were examined for antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The situation was quite different regarding diphtheria, as evidently most of the groups studied lacked adequate protection. In agreement with other reports, we also found a high proportion of non-protected adults [5,6,34,40,[48][49][50][51][52]. Indeed, the alarming percentage of non-protected mothers and children is of considerable concern.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The situation was quite different regarding diphtheria, as evidently most of the groups studied lacked adequate protection. In agreement with other reports, we also found a high proportion of non-protected adults [5,6,34,40,[48][49][50][51][52]. Indeed, the alarming percentage of non-protected mothers and children is of considerable concern.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, three categories of protection have been proposed [31,32] and currently adopted in serological surveys [22,[33][34][35]: fully protective (titers >0.1 IU/mt), partly protective (titer range 0.01-0.1 IU/ml) or non-protective (titers <0.01 IU/ml). Serum IgG anti-T antibody titers in 50 non-vaccinated infants (aged 1-1.4 month) and in infants (aged 3-7.8 months) who received one (n=25), two (n=25) or three (n=55) doses of DTP vaccine, as well as the percentages of protection within each group are shown in Table 1.…”
Section: Tetanus and Diphtheria Antibodiesmentioning
confidence: 99%
“…Evidence suggests that a large proportion of the disease among adults may have been transmitted from ill or asymptomatic children and that children played an important role in amplifying the overall epidemic, even in countries where most of the cases were reported among adults. Women had a much higher incidence of diphtheria than did men despite no evidence of lower serologic immunity [36]. In a case-control study in Ukraine, the risk among women was not significantly elevated after adjusting for age, vaccination history, and household size and composition, but having у2 school-age children in the household was associated with a significant increase in risk [37].…”
Section: Reasons For the Reemergence Of Epidemic Diphtheriamentioning
confidence: 93%
“…Only small outbreaks and isolated imported cases have been reported, despite the fact that seroepidemiological studies have shown insufficient protection, especially among the adult population (6,11).…”
mentioning
confidence: 99%